The end of agency and the last man - Jarl K. Kampen; Laurenc L. De Vita (The Central European Review of Economics and Management (CEREM), 2021)
Aim: In order to address the question whether a more sustainable society requires a change of purpose or a change of system, we must first resolve the issue of human agency. Is humanity free to choose its own destiny, or is humanity's future determined by contingency of conditions and choices of the past? Design / Research methods: On the basis of cumulated knowledge and carefully cited literature, we defend the thesis that human agency is at best a minor factor in the determination of the future even in the short term. Conclusions / findings: We conclude that significant decrease of resources depletion and greenhouse gas production may sustain humanity in the middle to long term, but the proven lack of human agency allows only to predict the complete demise of humanity in the short term. Originality / value of the article: We apply the method of dialogue to show historical points of focus with respect to the issue of human agency. This paper is of interest to those organizing projects of socio- and or geo-engineering, since it describes the likely limitations of agency in regards to social structure, and so implies that actions will always have unintended consequences, which will drive more actions.
Keywords: O10; O21; O33; O35; P18; P28; P41; Q40; Q50; 330; socio-engineering; geo-engineering; agency; climate change; systemic change; energy